Legal, Political Science, and Economics Approaches to Measuring Malapportionment: The U.S. House, Senate, and Electoral College 1790–2010. (29th October 2020) - Cervas, Jonathan; Grofman, Bernard
Abstract : Objective: We compare and contrast methods for measuring malapportionment from different disciplines: law, political science, and economics. Methods: With data from the U.S. House, Senate, and Electoral College (EC) over the period 1790–2010, we compare disproportionality measures and compare both across time and between institutions. Results: We demonstrate that which approach to measurement we take can dramatically affect some of the conclusions we reach. However, we also demonstrate that the House and the EC are hardly malapportioned, regardless of which measure we use, while the level of malapportionment we observe in the Senate can depend on which measure we use. Conclusion: Since there are many axiomatic properties we might wish to satisfy, no one measure is uniformly best with respect to all feasible desiderata. However, one measure, the minimum population needed to win a majority, offers a readily comparable measure across legislatures and jurisdictions, and is easy for nonspecialists to understand.